A SURVEY ON THE TEACHING OF WRITING AT SENIOR HIGH SCHOOLS IN RIAU PROVINCE - Eliwarti Eliwarti; Rumiri Aruan (International Journal of Educational Best Practices, 2018)
Abstract: Teaching writing in senior high schools provides students with knowledge, experience and strategies of writing simple texts to more complex ones. This research aims at looking at how writing skills are taught at senior high schools in Riau Province-Indonesia. Specifically, the research answers the research questions about teaching materials, methods/strategies used by English teachers in the teaching of writing and students’ attitude towards writing skills. The samples are second year English Department students of FKIP Riau University coming from different cities and regencies in Riau Province. The data were collected through distributing a set of questionnaire. The results show that most writing materials consist of linguistics knowledge such as sentence structure, vocabulary and punctuation and lack of writing skills and strategies like brainstorming, drafting, revising and editing. Moreover, most teachers are product oriented in their teaching of writing. Finally, most students (65.9) have low attitude towards writing skills. From these findings, it can be concluded that: writing materials need to be focussed on writing skills and strategies, teachers’ knowledge and skills on teaching methods/strategies need to be upgraded and students’ attitude towards writing skills needs to be improved. These findings can be used as a reference to do some improvement in the teaching of writing in senior high schools in Riau province.